The History of Christian thought - Hill, Jonathan (Downers Grove, Ill. InterVarsity Press, 2003)
Why read about the history of Christian thought? Because, if you are Christian yourself, it helps you to understand the faith--addressing everything from where Christians got their ideas of the Trinity and how Christ can be both human and divine to what
Keywords: Theology, Doctrinal -- History. Theology, Doctrinal. Doctrinal theology -- History